Implikasi Putusan No. 002/Puu-I/2003 terhadap Privatisasi Bisnis Migas - Syaiful Bakhri (The Constitutional Court of the Republic of Indonesia, 2011)
Statue no. 22/ 2001 on Oil and Gas. (Oil and Gas Law). Have reaped the problem, since the establishment, terms with the impact of globalization, as well as the world economic crisis. Therefore as new laws that regulate oil and gas, there has been a reform in the oil and gas law, as well as a variety of model settings. As is usually the administrative laws, tend to use the criminal provisions, in order to maintain, this thing is set, it can be done ideally, and improve the welfare of the people in business with the capital requirement migas.yang besar.Investasi multinational companies have long engaged in oil and gas, even since the colonial period, until today. Hence privatization of State-Owned Enterprises in the field of oil and gas business, must be strictly regulated, so that the model of economic democracy as provided for in the Constitution Article 33 of the Constitution of 1945, can be implemented with a high spirit of nationalism.